Acting Prime Minister Decree No. 74 Of The Year 2018 = قرار القائم بأعمال رئيس مجلس الوزراء رقم 74 لسنة 2018 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic